2003
DOI: 10.1121/1.1575751
|View full text |Cite
|
Sign up to set email alerts
|

Distortion product otoacoustic emission suppression tuning curves in normal-hearing and hearing-impaired human ears

Abstract: Distortion product otoacoustic emission (DPOAE) suppression measurements were made in 20 subjects with normal hearing and 21 subjects with mild-to-moderate hearing loss. The probe consisted of two primary tones (f2, f1), with f2 held constant at 4 kHz and f2/f1 = 1.22. Primary levels (L1, L2) were set according to the equation L1 = 0.4 L2 + 39 dB [Kummer et al., J. Acoust. Soc. Am. 103, 3431-3444 (1998)], with L2 ranging from 20 to 70 dB SPL (normal-hearing subjects) and 50-70 dB SPL (subjects with hearing los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
43
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 47 publications
(62 reference statements)
13
43
1
Order By: Relevance
“…4-8 are consistent with previous descriptions of DPOAE suppression in humans (Abdala, 1998(Abdala, , 2001Abdala et al, 1996;Abdala and Chatterjee, 2003;Abdala and Fitzgerald, 2003;Gorga et al, 2002aGorga et al, ,b, 2003Brown and Kemp, 1983;Kummer et al, 1995). Data from these studies showed the same dependence of growth of suppression on the relation between f 3 and f 2 .…”
Section: A Control Conditionssupporting
confidence: 82%
See 2 more Smart Citations
“…4-8 are consistent with previous descriptions of DPOAE suppression in humans (Abdala, 1998(Abdala, , 2001Abdala et al, 1996;Abdala and Chatterjee, 2003;Abdala and Fitzgerald, 2003;Gorga et al, 2002aGorga et al, ,b, 2003Brown and Kemp, 1983;Kummer et al, 1995). Data from these studies showed the same dependence of growth of suppression on the relation between f 3 and f 2 .…”
Section: A Control Conditionssupporting
confidence: 82%
“…These data are consistent with previous growth of suppression data based on auditory-nerve fiber responses in lower animals (e.g., Abbas and Sachs, 1976;Delgutte, 1990;Pang and Guinan, 1997) and are also consistent with measurements of suppression in basilar-membrane responses (e.g., Ruggero et al, 1992;Cooper and Rhode, 1996;Rhode and Cooper, 1993). Similar patterns have been observed in previous DPOAE suppression data as well (e.g., Abdala, 1998Abdala, , 2001Abdala and Fitzgerald, 2003;Abdala and Charterjee, 2003;Gorga et al, 2002Gorga et al, , 2003Kummer et al, 1995). Specifically, these previous studies showed that suppression grows most rapidly for suppressors lower in frequency than the signal frequency and that the growth of suppression decreases as suppressor frequency increases.…”
Section: A Control Conditionssupporting
confidence: 81%
See 1 more Smart Citation
“…6 might be consistent with the reduced differences between tip and tail thresholds as observed in frequency-threshold curves of auditory neurons (see, for example, Sewell, 1984), although we do not, as yet, have data that can be used to more directly test this hypothesis in humans. Tip-to-tail differences estimated from DPOAE suppression tuning curves have been interpreted as estimates of cochlear-amplifier gain (e.g., Pienkowski and Kunov, 2001;Mills, 1998;Gorga et al, 2002Gorga et al, ,2003. If the interpretation of the data shown in Figs.…”
Section: Slopes Of Dpoae I/o Functionsmentioning
confidence: 99%
“…Recent work has demonstrated that differences in distortion-product otoacoustic emission (DPOAE) suppression tuning curves (STCs) between ears with normal hearing (NH) and ears with hearing loss (HL) depend on the stimulus level at which comparisons are made (Abdala and Fitzgerald, 2003;Gorga et al, 2003;Gruhlke et al, 2012). When compared at equal stimulus-probe levels (primary levels for f 1 and f 2 , the stimulus frequencies eliciting the DPOAE) relative to threshold (i.e., sensation level, SL), STCs in ears with mild-to-moderate HL were characterized by reduced gain (as estimated by tip-to-tail differences) and broader tuning (based on the quality factor, Q), compared to ears with NH.…”
Section: Introductionmentioning
confidence: 99%